INFLUENCE OF LEVOTHYROXINE SODIUM ON GROWTH AND UPTAKE OF SOME MINERAL ELEMENTS IN COTTON (GOSSYPIUM HIRSUTUM L.) - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2012)
The aim of this study is to find out whether or not synthetic human thyroxine hormone has any effects on growth and mineral element distribution in plants. Levothyroxine is identical to the hormone thyroxine, which is produced naturally by the human thyroid gland. In human hypothyroidism, the thyroid gland becomes unable to produce normal amounts of thyroxine, and the level of both T-3 and T-4 (thyroid hormones) in the blood decreases. This results in a reduced rate of metabolism, leading to symptoms such as weight gain, intolerance to cold and tiredness. Levothyroxine is given to replace the thyroxine that would normally be produced by the thyroid gland. This restores levels of T-3 and T-4 to their normal state. Once the thyroid gland becomes unable to produce thyroxine, it will generally not return to normal function. When compared to some plant substances, this chemical shows some structural similarities. Therefore in this preliminary study, the effects of levothyroxine (Na form) on growth parameters stem length, leaf, stem and root fresh and dry weights, and leaf area and its influence on uptake of mineral elements such as Fe, Mg and Zn in cotton was studied. As a result, it was observed that some growth parameters increased or decreased related to the applied concentrations and Fe, Mg and Zn values were affected in leaf, stem and root parts of the treated cotton samples.
Keywords: SPARINGLY SOLUBLE PHOSPHORUS; CELL-WALL; GROUNDNUT ROOTS; EXCISED ROOTS; HIGHER-PLANTS; TRANSTHYRETIN; EVOLUTION; HYDROLYSIS; WHEAT; BORON